EXPLORATION OF THE RELATIONSHIP BETWEEN TRAINING, WORK EXPERIENCE, AND PROMOTION OF POSITIONS IN PEKANBARU MINING SECTOR COMPANIES - Safari, Surya; Fernandho, Michael; Hafni, Layla (Komunitas Manajemen Kompetitif, 2025)
This study aimed to determine the magnitude and significance of the training, work experience, and promotions on employee performance at Mining sector companies in Pekanbaru. The population of this research is company employees with a sample of 50 people taken with a saturated sampling technique, the analytical method used is Multiple Linear Regression Analysis with SPSS v20. The results of this study indicate that training has a significant impact on employee performance. Work experience has a significant impact on employee performance. Promotion has a significant impact on employee performance. To improve the performance of employees of Mining Sector companie in Pekanbaru should be able to review the training program and be able to pay more attention to the promotion of appropriate positions in the field and education so that employees are more loyal to Mining sector companies in Pekanbaru and can improve employee performance.